Investigating the aberration found in 4.438 MeV 12C photo peak of the Geant4 simulated prompt gamma spectrum. (June 2019) - Ramanathan, V; Peterson, S
Abstract: The purpose of this study is to investigate the broad 4.438 MeV 12 C photo-peak found in the Geant4 simulated prompt gamma spectrum from proton beam collision on a thin carbon target. The broad 4.438 MeV 12 C peak has been reported in previous work using the AFRODITE clover detector performing an absolute comparison of measured and simulated prompt gamma production for a carbon target in the proton therapeutic range. The simulated prompt gamma spectrum was obtained for a 95 MeV proton beam collision on the carbon target by counting the emitted prompt gammas over a 4ˇ solid angle using a Geant4(v10.01.p3) cross-section code with the suggested physics list for inelastic scattering in the proton therapeutic range (binary cascade model). This result was compared to prompt gamma spectra from other Geant4 inelastic scattering physics models. First, the default inelastic cross-section data set (Geisha) was compared to the Tripathi data set, producing basically identical spectra, indicating that the cross-section data set has no bearing on the binary cascade inelastic scatter model. Second, comparisons of the precompound model using an exciton number of 1 and the Geisha cross-section data set provides a 4.438 MeV photo peak that is closer to the experimental result. The precompound model with an exciton number of 1 and the default (Geisha) cross-section data set significantly narrowed the 4.438 MeV photo peak, giving the peak that most closely resembled measured data.